An Exploratory Study among Prospective Entrepreneurs in Dibrugarh and Tinsukia Districts of Upper Assam (India) - Sarmah, Suman (AMC Indian Journal of Entrepreneurship, 2017)
Entrepreneurship may be a significant choice among people to deal with the constantly growing unemployment situation particularly in the North Eastern Region of India. This calls for a detailed focus on the major reasons that may influence people to opt for an entrepreneurial living. So, this study has been attempted to identify such reasons for entrepreneurship in the Dibrugarh and Tinsukia districts of Upper Assam. Primary data was collected through a survey of 300 respondents who are prospective entrepreneurs in these districts. The study discovered that personal development and being independent are found to be the most important reasons for taking up an entrepreneurial career among most of the respondents irrespective of their educational qualification, place of residence, marital status, gender, and age. Still, other reasons like achievement of recognition in society, and better flexibility to look after family responsibilities may also be also important reasons. These may be accentuated in any self employment generation schemes among local people on the part of the Government or other agencies in these districts in the near future.